The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2006
DOI: 10.1007/s00425-006-0368-z
|View full text |Cite
|
Sign up to set email alerts
|

Modification of phenolic metabolism in soybean hairy roots through down regulation of chalcone synthase or isoflavone synthase

Abstract: Soybean hairy roots, transformed with the soybean chalcone synthase (CHS6) or isoflavone synthase (IFS2) genes, with dramatically decreased capacity to synthesize isoflavones were produced to determine what effects these changes would have on susceptibility to a fungal pathogen. The isoflavone and coumestrol concentrations were decreased by about 90% in most lines apparently due to gene silencing. The IFS2 transformed lines had very low IFS enzyme activity in microsomal fractions as measured by the conversion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
57
0
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(61 citation statements)
references
References 50 publications
3
57
0
1
Order By: Relevance
“…Accompanying this was the accumulation of relatively small amounts of liquiritigenin, the immediate precursor of daidzein. Recently, it was reported that cosuppression of IFS in soybean hairy roots led to the accumulation of p-hydroxybenzoic acid and vanillic acid in the soluble fraction (Lozovaya et al, 2007). However, these metabolites did not appear as major peaks in metabolic profiles of our IFS RNAi-silenced tissues.…”
Section: Silencing Of Isoflavone Synthase and Chalcone Reductase Is Hmentioning
confidence: 57%
“…Accompanying this was the accumulation of relatively small amounts of liquiritigenin, the immediate precursor of daidzein. Recently, it was reported that cosuppression of IFS in soybean hairy roots led to the accumulation of p-hydroxybenzoic acid and vanillic acid in the soluble fraction (Lozovaya et al, 2007). However, these metabolites did not appear as major peaks in metabolic profiles of our IFS RNAi-silenced tissues.…”
Section: Silencing Of Isoflavone Synthase and Chalcone Reductase Is Hmentioning
confidence: 57%
“…Additionally, compared with sugars, amino acids, and organic acids present in rhizodeposits, isoflavonoids (and other secondary metabolites) are species-specific and are more likely to recruit unique microbial communities. Silencing of isoflavonoid biosynthesis in the roots did not significantly influence other metabolites in the phenylpropanoid pathway, except the accumulation of liquiritigenin (the substrate of IFS), p-hydroxy benzoic acid, coumaric acid, and p-hydroxybenzaldehyde (Lozovaya et al 2007;Subramanian et al 2006) (data not shown). We cannot exclude the possibility that a small proportion of the changes in root bacterial profiles could be due to these relatively small changes in nontarget phenylpropanoids.…”
Section: Discussionmentioning
confidence: 92%
“…Isoflavones play important roles as signal molecules for inhibiting pathogen attacks (Lozovaya et al, 2007;Zabala et al, 2006) and for plant-microbe symbiotic interactions (Subramanian et al, 2006;Sugiyama et al, 2007). Genistin and daidzin is initiated by the conversion of the essential amino acid L-phenylalanine into p-Coumaroyl-CoA.…”
Section: Soybean Composition and Isoflavone Biosynthesismentioning
confidence: 99%